Evaluarea impactului auditului financiar asupra gestiunii finanţelor publice - Secrieru, Vasile; Mateoc – Sârb, Nicoleta (CEP USM, 2024)
The financial audit at the level of a public institution involves the audit of its financial statements or reports. In financial reports of public institutions it is reflected, the buget of the public institution consisting of the following blocks: income, expenses, non-financial assets, financial assets, liabilities and change in cash balance. These blocks are based on the elements of the budget classification, namely: organizational classification, functional classification, program classification, economic classification and source classification. Regardless, however, of the elements of the budget classification, they all reflect public finances. Therefore, in the process of assessing the impact of the financial audit, the author will consider the impact of the financial audit on the management of public finances. The audit results must reflect the conclusions and recommendations on the financial statements of the audited institution, so as to eliminate financial and management risks and improve the quality of financial reports.

Auditul financiar la nivelul unei instituții publice presupune auditul situațiilor sau rapoartelor financiare ale acesteia. În rapoartele financiare ale instituției publice este reflectat, bugetul instituției publice format din următoarele blocuri: venituri, cheltuieli, active nefinanciare, active financiare, datorii și modificarea soldului de mijloace bănești. Aceste blocuri sunt puse la baza elementelor clasificației bugetare și anume: clasificația organizațională, clasificația funcțională, clasificația programelor, clasificația economică și clasificația surselor. Indiferent, însă, de elementele clasificației bugetare, toate acestea reflectă finanțele publice. Prin urmare, în procesul de evaluare a impactului auditului financiar, autorul va lua în considerare impactul auditului financiar asupra gestiunii finanțelor publice. Rezultatele auditului trebuie să reflecte concluziile și recomandările asupra situațiilor financiare a instituției auditate, astfel încât să elimine riscurile financiare și de management și să îmbunătățească calitatea rapoartelor financiare.
Evaluation of the impact of the financial audit on the management of public finances
Keywords: public institutions; public finances; financial audit; financial reports; risk; budget classification; instituții publice; finanțe publice; audit financiar; rapoarte financiare; risc; clasificație bugetară